A post project evaluation avaloq banking system upgrade and replatforming project - Asilo, Kevin John E. (University of the Philippines Diliman, 2014)
Sofgen has recently completed an Avaloq banking system upgrade and replatforming project for Bank XYZ. The scope of this post project evaluation study is to understand whether the projects' management were effective, achieved its objectives, and the outcomes had an impact. This post project evaluation is a collection, record and information organization of results. This shall contain a report of short-term and immediate results from project artifacts gathered and questionnaires prepared. This shall demonstrate the effectiveness, efficiency and proper use of organizational resources (i.e. financial, human, etc.) recognize actual changes and progress made, identify areas that were successful and those that need further improvement and finally, validate for project members and stakeholders that desired outcomes have indeed been achieved. The author postulates that project success be measured not only against the traditional triple constraint of cost, time and scope, and recommends that objectives realization, and project team satisfaction with project management be considered as well. Recurring and key technology management issues on technology requirements gathering, resource availability and staff turnover, and project structure and organizational culture were identified and discussed. The author then recommends process improvements for future projects of Sofgen by providing a forensic review. These steps or process improvements are not prescriptive but rather indicative. At the end of the day, the company's management will dictate which steps will coincide with their strategy and which will help the company become more competitive and sustainable. Finally, recommendations for future research such as post-project evaluation after a longer time frame and business impact analysis and return-on-investment study was given.